Effects of Microcurrent on Oxygen Saturation by Controlling Rectus Abdominis Activity in Preterm Infant With Desaturation During Feeding: A Pilot Study - Kwon, Dong Rak; Kwon, Dae Gil; Jeong, Ji Eun (Frontiers in Pediatrics, 2021)
Objective: To determine whether a portable microcurrent therapy device (PMTD) of the rectus abdominis muscles is effective for treating desaturation during feeding in preterm infants and to evaluate the association between initial electrical activity of respiratory muscle and long-term development delay Methods: Twenty preterm infants with desaturation during feeding were recruited. Respiratory muscle activity was quantified by calculating the root mean square (RMS) of the electromyography. All preterm infants received a 30 min PMTD application to the rectus abdominis and diaphragm daily for 2 weeks. RMS of diaphragm and rectus abdominis, feeding volume, frequency of desaturation during feeding at baseline (pre-PMTD) and 1-,2-week post-PMTD were measured. The number of days it took to treat desaturation after PMTD was measured. A Denver developmental screening test was performed and infants were divided into 3 groups: 1) normal; 2) caution; and 3) delayed at 3months after PMTD. Results: The desaturation during feeding of all the preterm infants subsided after PMTD and the mean days took to treat desaturation was 25.4±14.2 days. The RMS of diaphragm, rectus abdominis, and frequency of desaturation during feeding were significantly decreased and the feeding volume was significantly increased after PMTD (p<0.01). The mean treatment duration for desaturation was negatively correlated with RMS of rectus abdominis at baseline and 1 week post-PMTD, respectively (Pearson’s correlation coefficient=-0.461, -0.514, p-value=0.047, 0.029). RMS of rectus abdominis of Group 3 is lower than that of group 1 and 2 (p<0.01). Conclusions: This pilot study showed that the microcurrent therapy of rectus abdominis is an efficient therapy for the treatment of preterm infants with desaturation during feeding, especially preterm infants with higher activity of the rectus abdominis. In preterm infants with lower rectus abdominis activity, more long time is required to treat desaturation by microcurrent therapy and developmental delay is observed at 3 months post-treatment.